Enzymatic hydrolysis ability and mechanical strength of cellulose fibres - Nazarov K.K., Qudratxudjayev M.A., Shukurxonova M.G (International Journal of Advanced Science and Technology, 2020)
The correlation between the mechanical strength and the enzymatic hydrolysis of cotton fibers was studied. In the course of research, it was proved that not strong, defective fibers (not suitable for industry) are more exposed to enzymes. Moreover, the stronger the fiber, the higher its technological properties, the higher the resistance of the fiber to biodegradation. It was also found that the fibers of diseased cotton plants are hydrolyzed at the highest rate compared to fibers of healthy plants. Moreover, the efficiency of enzymatic hydrolysis for some studied fiber samples can reach up to 77% in the yield of sugar substances. In addition, for the first time it was established that enzymatic hydrolysis is a characteristic feature of the strength of cotton fiber, which allows us to develop new biological criteria for assessing the strength of fiber in industry.